Understanding People’s Acceptance of Light Rail Transit in Bandung and Its Determinant Factors - Raisha Shadrina; Yuliani Dwi Lestari (Bina Nusantara University, 2019)
The aim of this research was to verify the readiness of Bandung people in accepting Light Rail Transit (LRT) as the new transport option. Through a survey questionnaire with various respondent backgrounds, the researchers applied statistical analysis using ANOVA to compare the acceptance between the group of gender, age, occupation, income, home location, mobility pattern, and current transport. As the extension, the research also explored the factor determining people’s priority in choosing transport and showing attributes (comfort, security and safety, exclusivity, time travel, cost, flexibility, facility, and accessibility). The result reveals that there are no differences between-group comparisons in accepting LRT as the new transport. In analyzing the determinant factors, the result shows that passengers tend to value security and comfort for their daily activities in choosing public transportation. Meanwhile, the exclusivity and facility are considered undesirable for passengers in deciding to take public transportation for travel. LRT is considered as a mode transport that provides sustainable transportation value. The readiness of passenger and market environment to the sustainable transportation option is important to maintain the successful implementation of the LRT project in Bandung.